Genome-Wide Association Study Identifies HLA-DP as a Susceptibility Gene for Pediatric Asthma in Asian Populations - Emiko Noguchi; Hiromi Sakamoto; Tomomitsu Hirota; Kaori Ochiai; Yoshimasa Imoto; Masafumi Sakashita; Fumitake Kurosaka; Akira Akasawa; Shigemi Yoshihara; Noriko Kanno; Yumi Yamada; Naoki Shimojo; et al. (2011)
Asthma is a complex phenotype influenced by genetic and environmental factors. We conducted a genome-wide association study (GWAS) with 938 Japanese pediatric asthma patients and 2,376 controls. Single-nucleotide polymorphisms (SNPs) showing strong associations (P<1×10−8) in GWAS were further genotyped in an independent Japanese samples (818 cases and 1,032 controls) and in Korean samples (835 cases and 421 controls). SNP rs987870, located between HLA-DPA1 and HLA-DPB1, was consistently associated with pediatric asthma in 3 independent populations (Pcombined = 2.3×10−10, odds ratio [OR] = 1.40). HLA-DP allele analysis showed that DPA1*0201 and DPB1*0901, which were in strong linkage disequilibrium, were strongly associated with pediatric asthma (DPA1*0201: P = 5.5×10−10, OR = 1.52, and DPB1*0901: P = 2.0×10−7, OR = 1.49). Our findings show that genetic variants in the HLA-DP locus are associated with the risk of pediatric asthma in Asian populations.